Cracking the code: Social and contextual cues to language input in the home environment. (31st August 2020) - Custode, Stephanie A.; Tamis‐LeMonda, Catherine
Abstract: Infants use social cues like gaze and touch, typically during joint attention with caregivers, to decipher word meaning. Yet, studies on cues to word meaning primarily rely on structured tasks, where distractors are few compared to the countless objects that vie for attention in the home environment. Forty mothers and their 13‐month‐old infants were video‐recorded during home routines. From transcripts, 3, 000+ "naming events" were coded for social (visual and manual) and contextual (location: room and place) cues to the object of reference. Mother and infant visual and tactile attention accompanied naming events with high regularity, and the objects mothers named were specific to room and place. Nested social and contextual cues infuse infants' everyday language experiences in ways that help infants disambiguate word meaning.